2021
DOI: 10.1186/s13073-021-00936-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of the nonconjugative virulence plasmid from hypervirulent Klebsiella pneumoniae

Abstract: Background Klebsiella pneumoniae, as a global priority pathogen, is well known for its capability of acquiring mobile genetic elements that carry resistance and/or virulence genes. Its virulence plasmid, previously deemed nonconjugative and restricted within hypervirulent K. pneumoniae (hvKP), has disseminated into classic K. pneumoniae (cKP), particularly carbapenem-resistant K. pneumoniae (CRKP), which poses alarming challenges to public health. However, the mechanism underlying its transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 47 publications
3
53
1
1
Order By: Relevance
“…In this study, the p1632-2 plasmid was typed as IncM2 plasmid and had an extremely high-conjugative frequency, higher than the other IncM2- armA plasmid pMS3802OXARMA studied before (10 −1 versus 10 −4 ) ( 25 ). As previous studies described ( 19 , 26 ), the oriT -positive plasmid could be cotransferred with the conjugative plasmid, and the p1632-1 plasmid ( oriT and relaxase protein positive) still holds the potential to be mobilized when p1632-2 is induced.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, the p1632-2 plasmid was typed as IncM2 plasmid and had an extremely high-conjugative frequency, higher than the other IncM2- armA plasmid pMS3802OXARMA studied before (10 −1 versus 10 −4 ) ( 25 ). As previous studies described ( 19 , 26 ), the oriT -positive plasmid could be cotransferred with the conjugative plasmid, and the p1632-1 plasmid ( oriT and relaxase protein positive) still holds the potential to be mobilized when p1632-2 is induced.…”
Section: Discussionmentioning
confidence: 58%
“…Plasmid conjugation experiments were performed on the mcr-1 -harboring E. fergusonii strains as described previously ( 34 ). A sodium azide-resistant E. coli strain J53 was used as the recipient.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Xu et al ( 21 ) reported that virulence plasmid of ST11 hvKp could transfer via coexisting conjugative IncF plasmids using shared oriT regions. Additionally, a specific 28-bp fusion site located in the virulence plasmid of ST11 hvKp could assist with the virulence plasmid forming a hybrid plasmid with conjugative IncF plasmids and then be cotransferred.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that ST11 CR-hvKp possessed five tandem repeats of the bla KPC-2 ::NTEKPC-Id fragment within the IncR plasmid was also mediated by the IS 26 ( 35 ). More importantly, with the help of the IncF plasmids, the nonconjugative virulence plasmid could achieve the mobilization among Enterobacterales strains ( 21 ). IS 26 was closely related to the IncFII plasmid replication among the ST23 K. pneumoniae , alarming that the transformation and conjugation among these organisms should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation